A Novel Structure for Vector Control of Symmetrical Six-Phase Induction Machines with Three Current Sensors - Nabi, H. P.; Dadashi, P.; Shoulaie, A. (Engineering, Technology & Applied Science Research, 2011)
Vector control is one of the most popular multiphase induction machine drive methods due to its dynamic performance. Since all phase currents are needed in vector control drive, by increasing phase numbers, the number of required current sensors increases which is one of the disadvantages of vector control in multiphase machine drives. In this paper vector control of a symmetrical six-phase induction machine with a novel configuration is presented. The aforementioned configuration is designed in a simple way that only three current sensors will be needed. Analytical equations are extracted in this paper to show that some of current components which do not contribute in torque production will be eliminated due to the proposed scheme. Simulation and experimental results are provided to verify the benefits of the proposed configuration.